2016
DOI: 10.1007/s12325-016-0288-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy and Safety of Insulin Detemir and Insulin Glargine in Hospitalized Patients with Type 2 Diabetes: A Randomized Crossover Trial

Abstract: When both basal insulin analogs were given once daily in T2D, insulin detemir achieved similar efficacy to insulin glargine. On the other hand, there may be differences in action of the compared basal insulins. Further studies with larger patient samples are necessary to support evidence and reveal possible mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Based on these studies, the use of basal insulin analogs -glargine and detemir- has become the preferred insulin formulations in the hospital setting. Two studies have compared treatment with glargine and detemir in the management of hospital hyperglycemia in general medicine and surgery patients with type 2 diabetes (20, 21). Zhang et al (20) conducted a short crossover study in 42 patients with type 2 diabetes treated with detemir and glargine insulin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these studies, the use of basal insulin analogs -glargine and detemir- has become the preferred insulin formulations in the hospital setting. Two studies have compared treatment with glargine and detemir in the management of hospital hyperglycemia in general medicine and surgery patients with type 2 diabetes (20, 21). Zhang et al (20) conducted a short crossover study in 42 patients with type 2 diabetes treated with detemir and glargine insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have compared treatment with glargine and detemir in the management of hospital hyperglycemia in general medicine and surgery patients with type 2 diabetes (20, 21). Zhang et al (20) conducted a short crossover study in 42 patients with type 2 diabetes treated with detemir and glargine insulin. There were no differences in the number of days to achieve target BG (4.0 ± 0.5 days vs. 3.3 ± 0.4 days, p = 0.286) or in total daily insulin dose (30.1 ± 2.4 U vs. 30.1 ± 2.9 U, p = 0.99) between insulin detemir and insulin glargine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a limited number of studies on head-to-head comparison of iDet and iGla in patients with T1D [4,5]. All the comparison studies conducted on patients with either T1D or type 2 diabetes (T2D) also used once-daily dosing of these two basal insulin analogues and demonstrated similar efficacy [5][6][7]. In the only available trial that compared once-versus twice-daily iDet in patients with T1D, the HbA1c at four months was 8.1 ±0.9 vs. 8.0 ±1.0% with once-and twice-daily iDet, respectively, with an adjusted between-group difference of 0.12%, showing noninferiority for once-daily dosing [8].…”
mentioning
confidence: 99%
“…There are no human studies on pharmacokinetics or outcomes of using detemir in hypoalbuminemic patients. Randomized controlled studies of detemir versus glargine have not found a difference in hypoglycemia (6)(7)(8)(9), but these trials included only a few hundred patients who probably were not hypoalbuminemic. A recent retrospective study found a higher rate of hypoglycemia (,70 mg/dL) in determir-treated compared to glargine-treated inpatients (10).…”
mentioning
confidence: 99%